Analisis Wacana Kritis Tanggapan Megawati terhadap Persoalan Kelangkaan Minyak Goreng - Alamsyah, Dani; Mayasari., Mayasari.; Lubis, Fardiah Oktariani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Megawati Soekarnoputri is the 5th former president of Indonesia and currently serves as chairman of the PDIP party. As an influential politician in Indonesia, all his actions and words can influence public opinion. At the online webinar entitled "Prevent Stunting for Golden Generation", Megawati alluded to the condition of the people who are facing the problem of scarcity of cooking oil. He responded to this problem by assuming that the community's reaction was excessive regarding the problem of scarcity of cooking oil. As a result of her response, Megawati received various criticisms from the public through various media. This research will focus on Megawati's response with the aim of knowing linguistic elements, the process of text production and consumption, as well as the socio-cultural conditions of society. This qualitative research uses the critical discourse analysis model of Norman Fairclough which divides the analysis into three dimensions, namely text analysis, discourse practice analysis and sociocultural analysis. The research results show that there are several cohesions and coherences that shape discourse and diction which indicate the communicator's view of the audience, the process of text production and consumption goes according to the topic being discussed but there are statements that make some groups feel unacceptable and the way of delivery is not wearing it, and social and cultural background that influences the formation of discourse and the response it receives because the discourse has something to do with sociocultural situations. Keywords : Critical Discourse Analysis, Megawati, Discourse.